PELAKSANAAN WEWENANG KOMISI PENYIARAN INDONESIA DAERAH (KPID) PROVINSI RIAU BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2002 TENTANG PENYIARAN - Arsy Rahma Nelly; Mexsasai Indra; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In order to deliver information, entertainment, and other broadcasts were presented by television in its implementation until today there are still many broadcasts that do not meet broadcast standards, such as the scenes that are not worthy to be displayed and viewed by children. To oversee each of the broadcast, the state through Act No. 32 of 2002 on Broadcasting shall authorize the Indonesian Broadcasting Commission (KPI) contained in every region in Indonesia, namely the Regional Indonesian Broadcasting Commission (Commission). The purpose of this thesis, namely, first, how the authority of Regional Indonesian Broadcasting Commission (Commission) of Riau Province in Overseeing Broadcast Television by Act No. 32 of 2002 on Broadcasting, Second, what are the constraints and efforts faced by the Regional Indonesian Broadcasting Commission ( Commission) Riau Province in exercising its authority Oversee Television Broadcast by Act No. 32 of 2002 on Broadcasting.Regional Indonesian Broadcasting Commission (Commission) Riau is expected to improve its performance in monitoring television broadcasts, Second, Act No. 32 of 2002 on broadcasting should be revised due to impose administrative sanctions and exercised its powers Indonesian Broadcasting Commission (KPI) Central and Regional Indonesian Broadcasting Commission (broadcasting) Videos must be coordinated in advance to the Government that the Ministry of Communications and Inforrmasi in licensing broadcasting operators and termination of licenses broadcasters, it does not show as an independent institution and broadcasting regulator.Keywords: KPID - Implementation - Authorities